(untitled) (Bangladesh Journal of Child Health, 2017)
Background: Proper feeding practices during the first two years of life is essential for growth nutrition and development of young children. Optimum infant and young child feeding can reduce childhood mortality and morbidity significantly. Present study was done to know the infant and young child feeding pattern in the children of 0-23 months of age attending out patient department of an urban hospital. Methods: This cross sectional study was conducted among 314 mother/child pair attending the outpatient department of an urban hospital during the period of September 2014 to December 2014. Result: 68.5% children had early initiation of breast feeding and exclusive breast feeding among children below 6 months was 66.8%.Continued breast feeding among the children of 12 to 15 months was 80.4% and 84.2 % children were given solid food at 6 months of age. Adequate minimum dietary diversity, minimum meal frequency and minimal acceptable diet among children 6-23 months were 61.4%,57.3% and 39.4% respectively.64.5%% children were taking iron rich food or supplementation. Conclusion: Early initiation of breast feeding(0-23mo) and Exclusive breastfeeding(0- 6mo) were satisfactory in the study children but IYCF practice in children of 6-23 months was not optimum and far away from the HPNSDP 2011-2016 target of 52% of children to be fed with minimum acceptable diet. Bangladesh J Child Health 2016; VOL 40 (2) :92-97